2014
DOI: 10.1016/j.tox.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Lead induces COX-2 expression in glial cells in a NFAT-dependent, AP-1/NFκB-independent manner

Abstract: Epidemiologic studies have provided solid evidence for the neurotoxic effect of lead for decades of years. In view of the fact that children are more vulnerable to the neurotoxicity of lead, lead exposure has been an urgent public health concern for decades of years. The modes of action of lead neurotoxic effects include disturbance of neurotransmitter storage and release, damage of mitochondria, as well as induction of apoptosis in cerebrovascular endothelial cells, astroglia and oligodendroglia. Our studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In the peripheral tissues, COX-1 is a constitutive form of cyclooxygenase, while COX-2 is an inducible form [49]. In contrast, COX-2 is the basic form expressed in neurons [50,51,52].…”
Section: Effects Of Pb On Enzymesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the peripheral tissues, COX-1 is a constitutive form of cyclooxygenase, while COX-2 is an inducible form [49]. In contrast, COX-2 is the basic form expressed in neurons [50,51,52].…”
Section: Effects Of Pb On Enzymesmentioning
confidence: 99%
“…In pathological conditions, such as hypoxia/ischemia and seizures, as well as neurodegenerative diseases including Alzheimer’s disease (AD), it has been demonstrated that over expression of COX-2 is associated with neurotoxicity [54]. Wei et al [49] investigated the effect of various doses of Pb (from 25 to 100 μM) on the induction of COX-2 in rat C6 glioma cells, mouse BV2 microglia, in primary cultures of cortex neurons, in neural stem cells (NSCs) and RBE4 cells (brain endothelium). The results of that research showed that Pb causes an induction of COX-2 in C6, BV2, primary culture of cortical neurons and NSCs [45].…”
Section: Effects Of Pb On Enzymesmentioning
confidence: 99%
See 3 more Smart Citations